2019
DOI: 10.3389/fmicb.2019.02083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 1,000 Type-Strain Genomes Improves Taxonomic Classification of Bacteroidetes

Abstract: Although considerable progress has been made in recent years regarding the classification of bacteria assigned to the phylum Bacteroidetes, there remains a need to further clarify taxonomic relationships within a diverse assemblage that includes organisms of clinical, piscicultural, and ecological importance. Bacteroidetes classification has proved to be difficult, not least when taxonomic decisions rested heavily on interpretation of poorly resolved 16S rRNA gene trees and a limited number of phenotypic featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
201
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,334 publications
(211 citation statements)
references
References 610 publications
(967 reference statements)
8
201
0
2
Order By: Relevance
“…maritima [11]. The genus is one of the many included in a recent phylogenomic study of the phylum Bacteroidetes [12] and has not been affected by the reclassifications therein proposed.…”
Section: Full-textmentioning
confidence: 99%
“…maritima [11]. The genus is one of the many included in a recent phylogenomic study of the phylum Bacteroidetes [12] and has not been affected by the reclassifications therein proposed.…”
Section: Full-textmentioning
confidence: 99%
“…2 Priority number assigned according to the date the documentation and request for validation are received. 3 The journal in which the name was effectively published does not have continuous pages. 4 In the genus protologue, the name of the type species was misspelled Albibacterium bauzanensis.…”
Section: Priority 2 Referencementioning
confidence: 99%
“…litoralis KMM 3912 T , phylogenetic placement based on both the 16S rRNA genes and the genomes indicated the independency of strain KK4 T from type species of the neighbouring genera Ulvibacter , Marixanthomonas , Marinirhabdus , Aureitalea and Aequorivita (Figs 1 and 2). A recent comprehensive survey of the genomic phylogeny of the family Flavobacteriacea also demonstrated that Ulvibacter , Marinirhabdus , Aureitalea and Aequorivita formed one phylogenetic cluster (UMA cluster) [52]; however, strain KK4 T formed a branch independent from the UMA cluster ( and S1). Moreover, AAI values also support the phylogenetic distinctiveness of strain KK4 T from type strains in the UMA cluster ().…”
Section: Taxonomic Conclusionmentioning
confidence: 99%